Implementasi Program Bina Keluarga Remaja (BKR) dalam Menekan Kasus Stunting di Kecamatan Kuta Selatan - Ni Putu Glory Damayanti; I Dewa Ayu Putri Wirantari; I Putu Dharmanu Yudharta (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
Youth Family Development (BKR) is a program in the form of outreach supported by group cadres in their respective regions which targets teenagers directly or parents who will or already have teenagers aged 10-24 years in increasing the understanding of parents in a family regarding the sustainable growth and development of teenage children, especially in the teenage aspect so that it does not create stunted toddlers in the future. The aim of this research is to find out and describe the implementation of the Youth Family Development (BKR) program in reducing stunting cases in South Kuta District, because South Kuta is the District with the highest number of stunted toddlers, namely 87 cases in Badung Regency in 2023. This research uses Qualitative methods, as well as through Program Implementation theory according to Charles O. Jones (1996:166) quoted by Faridha Nur Islam (2023), the results of this research are in The implementation of the Youth Family Development (BKR) program in reducing stunting cases in South Kuta District did not achieve good results on all existing indicators, namely organization, interpretation, and application/implementation. The ineffective implementation of the Youth Family Development (BKR) program in reducing stunting cases in South Kuta District is influenced by several things, namely lack of human resources, low commitment between sectors, and lack of participation of Youth Family Development (BKR) group cadres.